Reading the Fourth Gospel in the COVID-19 pandemic context - Thomaskutty, Johnson (HTS teologiese studies, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic situation persuades a reader of the Fourth Gospel to interpret the Scripture in new lights. In the contemporary context, the gospel of John has the potential to attune the attention of the reader towards the existential struggles of the people with myriad interpretative possibilities. The Jews often twinned sinfulness and sickness together, and in that light, they considered Jesus as a social sinner and his followers as a diseased community. The Johannine narrator realigns the struggles of the Sitz im Leben Kirche dynamically within the Sitz im Leben Jesu to present his defensive rhetoric. The Johannine community was composed of those who suffered quarantine, social isolation, sicknesses, resource deficiencies and continuous cleansing processes in the socio-religious and politico-cultural setting of their life. Jesus as the creator of the universe and the giver of life provides them hope in the midst of suffering and liberates them from the clutches of dehumanisation and marginalisation. A realignment of the Sitz im Leben COVID-19 within the framework of the Sitz im Leben Jesu/Sitz im Leben Kirche would guide us during the difficult times.Contribution: This article contributes to the reader a wider hermeneutical framework and a new way forward in interpreting the Fourth Gospel by taking into consideration the ongoing struggle of humanity across the globe during the COVID-19 pandemic situation. As a narrative, contextual and theological interpretation of the Fourth Gospel, the current article fits well within the scope of HTS Teologiese Studies/Theological Studies.